Use of demolition waste to reduce cement usage in cement composite - Mohd Khairi Abdul Aziz (Penerbit Universiti Malaysia Perlis, 2011)
As a developing country, construction is one of the main incomes producing in Malaysia. Huge amount of demolition waste were produced from these activities. In Malaysia, the construction waste has cause a significant impact on the environmental and also increasing the concern of the society and the waste generation is found to be in an increasing trend. These demolition wastes are disposed illegally or disposed at landfill. This study is to examine the suitability of demolition waste produced used to replace cement in concrete composition.Features such as specific gravity, and elemental composition were studied.